PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI LAPAS KELAS IIB PAYAKUMBUH - Kevin Rahmahesa Rihendry; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
The study aimed to examine the effect of compensation and transformational leadership on performance through work motivation as an intervening variable. The sampling method used is a saturated sampling technique that is, taking samples as a whole or all members of the population are used as samples. Respondents in this study were civil servants of Lapas Class IIB Payakumbuh amounting to 23 civil servants. This study used descriptive and statistical analysis methods conducted validity tests, rehabilitation tests, multicollinearity tests, heteroskedestity tests, normality tests, correlation tests, determination coefficients, t tests, path analysis, and sobel tests. The tests in the t test showed that compensation had a positive and significant effect on work motivation in employees of Class IIB Payakumbuh Prison, transformational leadership had a positive and significant effect on work motivation, compensation had a positive and significant effect on performance, transformational leadership had no effect on performance, Transformational leadership has no effect on performance, work motivation has a positive and significant effect on performance, work motivation can mediate between compensation and performance, and work motivation can mediate between transformational leadership and performance.